New spin structure constraints on hyperfine splitting and proton Zemach radius - David Ruth; Karl Slifer; Jian-Ping Chen; Carl E. Carlson; Franziska Hagelstein; Vladimir Pascalutsa; Alexandre Deur; Sebastian Kuhn; Marco Ripani; Xiaochao Zheng; Ryan Zielinski; Chao Gu (Physics Letters B)
The 1S hyperfine splitting in hydrogen is measured to an impressive ppt precision and will soon be measured to ppm precision in muonic hydrogen. The latter measurement will rely on theoretical predictions, which are limited by knowledge of the proton polarizability effect Δpol. Data-driven evaluations of Δpol have long been in significant tension with baryon chiral perturbation theory. Here we present improved results for Δpol driven by new spin structure data, reducing the long-standing tension between theory and experiment and halving the dominating uncertainty in hyperfine splitting calculations.